Manajemen Pendidikan Islam Budaya: Historisitas, Konsepsi dan Aktualisasi Manajemen Pendidikan Agama Islam Transformatif - Yohanik, Yohanik (Lembaga Yasin AlSys, 2023)
This paper uses a mixer methodology, first with literature review and second with field studies, the theme raised is Islamic Education Cultural Management: History, Conception, and Management of Transformative Islamic Education Actualization, in this paper there are three fundamental questions; first, what is the concept of Cultural Management of Islamic Education in Islam. Second, what is the history, conception of Islamic religious education management, Islam, transformative culture in Indonesia and third, what is the contribution of Islamic education management in a transformative Islamic culture in the Islamic education space in Islam in Indonesia. Which is where teacher supervision is a definite process. Furthermore, culture becomes part of the culture of the local community which cannot be separated from the language of the community. Culture (often called local wisdom) will be passed down through generations through oral stories. Islamic religious education based on truth and nobility, distancing oneself from unreal thoughts, even far from the origins of unpleasant behavior or influence. Islamic religious leadership education is important for moral (character)/ethics is easy), then the soul (emotional realm) is not only a cognitive and psychomotor realm, but 4) synergizes with culture, Islamic religious education, and tourism, and needs to be developed in a coordinated mannerin Islamic religious education with real regional characteristics